ELECTROCHEMICAL LYSIS IN ONCOLOGY: LITERATURE REVIEW - E. V. Anikanova; G. P. Guens; K. B. Kolontarev; S. A. Muslov (Сибирский онкологический журнал)
Recently, minimally invasive treatment modalities based on the application of various physical factors have been widely used in anticancer therapy. Electrochemical lysis is a method in which tumor cells are destroyed by local exposure to a constant low voltage electric current.Purpose: to present the current results of using electrochemical lysis in the treatment of various tumors, to describe the mechanism of tumor destruction and methods of delivering electric current to the tumor, as well as to evaluate the electrical parameters and positioning of the electrodes.Material and Methods.aliterature search included the Medical literatureanalysis and Retrieval system Online (Medline), the excerpta Medica data Base (embase), Web of science, scopus, Russian citation index. All articles were published before december 2019. The review included studies on the investigation electrochemical lysis in vitro, in vivo, as well as clinical observations and clinical studies in which electrochemical lysis has been used as an independent treatment, or in combination with other methods of anticancer treatment since 1984.Results. This review provides information regarding the electrochemical mechanisms of tumor destruction, anti-tumoral effects of electrochemical therapy, methodology for planning and distributing the dose of electrical lysis and positioning of electrodes. We have evaluated complications and oncological results. Electrochemical lysis is a safe, simple, effective, and relatively non-invasive method of antitumor treatment.Conclusion. The electrochemical lysis is a promising minimally invasive method which can be used for the treatment of tumors. However, long-term data are needed to validate this treatment before it can be included into clinical recommendation for the treatment of cancer patients.